2012
DOI: 10.1007/s00467-012-2331-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum cystatin C predicts acute kidney injury in preterm neonates with respiratory distress syndrome

Abstract: sCysC is an independent predictor of AKI in preterm neonates with RDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 38 publications
1
26
1
2
Order By: Relevance
“…Elmas et al (24) found that serum cystatin C is an independent predictor of AKI in premature newborns with respiratory distress syndrome. Kandasamy et al (25) analyzed 10 studies that assessed the sensitivity of cystatin C as an early biomarker of AKI in neonates and found that it can be successfully used for evaluation of renal function in sick neonates (sepsis-induced AKI and congenital renal anomalies).…”
Section: Discussionmentioning
confidence: 99%
“…Elmas et al (24) found that serum cystatin C is an independent predictor of AKI in premature newborns with respiratory distress syndrome. Kandasamy et al (25) analyzed 10 studies that assessed the sensitivity of cystatin C as an early biomarker of AKI in neonates and found that it can be successfully used for evaluation of renal function in sick neonates (sepsis-induced AKI and congenital renal anomalies).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of recent advances in renal replacement therapies, mortality of AKI remains high (25% -78%) (2,6). It occurs in 44% -78% of patients with neonatal septicemia, and the risk is 2 -3 times higher in these patients, compared to those without AKI (3,14).…”
Section: Serum Phmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a frequently encountered problem among ill neonates, admitted to neonatal intensive care units (8% -24%) (1,2). Decreased renal perfusion, low glomerular filtration rate, increased renal vascular resistance, and high plasma renin activity are major predisposing factors for acute renal impairment in the first days of life (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies correlated renal functional status using pRIFLE criteria with renal biomarker (uCysC and uIL-18) 19,20 . As this biomarker are not widely available and costly, this study correlated renal impairment using pRIFLE criteria with Apgar score in asphyxiated neonate , so that renal impairment can be predicted early by low Apgar score in perinatal asphyxia.…”
Section: Discussionmentioning
confidence: 99%